A Review Of The Application Of Sanctions For Maltreatment - Jumra Jumra (STIE Amkop Makassar, 2023)
The monoist view of the offense is to state the elements of criminal acts with criminal responsibility. This school believes that if there is an offense then there is a person who must be punished. So all elements of the offense are the same as the conditions for the person to be sentenced. Monoism emphasizes that if one of the elements of the offense is missing, then no one can be convicted. This research is descriptive research, namely research intended to describe the application of criminal sanctions against perpetrators of ordinary maltreatment offenses in Barebbo District. When viewed from the title of this research, this research uses the type of empirical legal research intended to describe theories that are empirical in nature, especially regarding the application of criminal sanctions against perpetrators of ordinary maltreatment offenses in Barebbo District. The application of criminal sanctions against perpetrators of ordinary maltreatment in Barebbo Sub-District, Bone Regency is in accordance with the Criminal Code. However, the sentences imposed by judges are sometimes very lenient, so it is feared that it will not have a deterrent effect and make it possible for the perpetrators to reoffend. Make forced efforts by using violence such as paralyzing actions for suspects who resist if it has reached a level that endangers the lives of officers and the public.